Climate change mitigation and agriculture - Wollenberg, Eva (Earthscan LondonGB, 2012)
Reviews the state of agricultural climate change mitigation globally, with a focus on identifying the feasibility, opportunities and challenges for achieving mitigation amon smallholder farmers.